The Source of Our Information regarding the Life of Jesus - Miller, Lucius Hopkins (The biblical world, 1913)
For the past three years the historicity of Jesus has been discussed with increasing freedom. And in very truth it is a matter of supreme importance. But the questions the discussion has raised are not to be settled by ingenious guesses patchworked together into academic theses. "Back to the sources!" That is the one reliable watchword. And the sources? Professor Miller discusses them sanely and constructively.